The Muslim Woman Discourse in the Ukrainian Soviet Press of the 1920 -1930s - Khamedova, Olha; Rosinska, Olena; Zhuravska, Oksana; Balabanova, Katerina (Journal of History Culture and Art Research, 2020)
The article analyzes the Muslim woman discourse in the Ukrainian Soviet press of the 1920-1930s. It is the publications in the newspapers about the women of the Soviet Union East that are of significant interest in the study of the feminist movement history. The purpose of the research is to analyze newspaper texts of the Soviet period to deconstruct their propagandistic content and to characterize the real state of the Muslim woman. The merit of the Ukrainian journalists is that they called attention to the issues of women’s life in Central Asia, Caucasus, Transcaucasus, and Crimea of that time. The key aspects highlighted by the press are family abuse, judicial absence of rights, and illiteracy. The Ukrainian press of the 1920s stated a hard dependent state of the Muslim woman in the family and in the society in the pre-Revolution past, it announced the life enhancement for women in the Soviet present. In the 1930s, the press focused on the “emancipated” Muslim women. The issues of women’s everyday life, daily routine, and health lacked the attention of journalists. An ideological component in the publications about women of the Soviet Union was important. Communist propaganda stressed that women’s emancipation is a part of the international proletarian movement for social liberation. The woman was of no value as an independent personality, she was considered as a resource, which can be used to consolidate the Soviet regime in regions and to spread communist propaganda. The press of that time formed a stereotype about the woman of the East as a victim of gender-based discrimination, who was not able to overcome that independently, without the help of the Soviet authorities.